Vanadium acid-reducing leaching from the fly ash of a thermal power plant - Igor V. Mishin; Alexey V. Nistratov; Roman D. Pichugov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2025)
Relevance. Due to the higher initial vanadium content in secondary sources compared to ore deposits, its extraction from the former appears to be a more cost-effective and resource-saving process. Fly ash from burning liquid fuels containing 1.9 wt % vanadium can be considered as a promising secondary source of this metal, which is essential in the production of high-strength alloys, catalysts, and electrolytes for flow batteries. A sufficiently complete extraction and simultaneous recovery of vanadium from the mentioned ash requires research and optimization of the corresponding transformations. Aim. Development of vanadium leaching from the fly ash of thermal power plant with sulfuric acid and reducing agent sodium sulfite. Methods. Methods of chemical experiment, photometric and atomic emission analysis of metals, analysis and interpretation of the results. Results and conclusions. This study proposes a method for leaching vanadium from ash using a solution of sulfuric acid and the reducing agent sodium sulfite, enabling to obtain a concentrate of vanadium (IV) in the form of VOSO4 for its further selective extraction. The addition of Na2SO3 during leaching facilitates the reduction of V(V) to V(IV), as confirmed by spectrophotometric analysis of the concentrate. On the other hand, leaching with sulfuric acid alone leads to vanadium extraction in the pentavalent form. Leaching efficiency was investigated by studying such factors as sulfuric acid concentration, reducing agent concentration, liquid/solid phase ratio, leaching time, and temperature. Our findings show that vanadium (>80%) and nickel (>65%) are predominantly recovered from fly ash, while iron and manganese mostly remain in the solid residue. The highest extraction efficiency (99,6%) for vanadium was achieved when simultaneous treating ash with a solution of 1 М H2SO4 and 0,04 M Na2SO3 at 80°C for 30 minutes with ash ratio of 4 ml/1 g. Nearly complete vanadium transition from ash to solution was achieved by washing the residue three times with distilled water at a ratio of 6 ml/1 g of ash. The resulting leaching solution contains ions of iron, vanadium, nickel and manganese in concentrations of 5.27, 1.87, 0.58 and 0.031 g/l respectively and requires separation by physical and chemical methods.